Multimodal Pain Management for Major Joint Replacement Surgery. (March 2019) - Goode, Victoria M.; Morgan, Brett; Muckler, Virginia C.; Cary, Michael P.; Zdeb, Christine E.; Zychowicz, Michael
Abstract : Effective pain management for orthopaedic major joint replacement is key to achieving earlier recovery, better functioning, and high rates of patient satisfaction. In an effort to decrease opioid dependency, practitioners are turning to multimodal pain management, which involves the use of multiple analgesic agents and techniques. To utilize this technique, a patient's history of and preoperative consumption of medications to treat pain impacts the success of this regimen. Multimodal pain management involves the use of nonsteroidal anti-inflammatory drugs, acetaminophen, N -methyl-D-aspartate antagonists, gabapentin, serotonin inhibitors, regional techniques, and opioids as needed. It is necessary for the nurse to understand the mechanism of pain and how the multimodal adjuncts target the pain response to benefit the patient's perioperative course as well as his or her postoperative and discharge management.